Exploring Business Sustainability Factors of Malaysian Agribusiness Small Medium Enterprises (ASMEs) - Nalini Arumugam; Alageasan Dhayalan; Fakhrul Anwar Zainol; Bonaventure Boniface (2020)
Business sustainability is a new field of interest among business scholars. Its conceptual ambiguity and lack of sector specific study had motivated this research. The aim of this study is to explore the factors associated with business sustainability of Malaysian Agribusiness Small Medium Enterprises (ASMEs). A total of 100 respondents from six states throughout Malaysia participated in this study by answering Likert scale questions. A theoretical framework consisting of one dependent and seven independent variables were rectified using the exploratory factor analysis (EFA) method. As a result, the instrument was identified adequate and reliable to explore seven (7) factors that influence business sustainability among Malaysian ASMEs, including (i) business passion and motivations, (ii) owner and business traits, (iii) business planning, (iv) organisational management, (v) resource management, (vi) production and marketing management and (vii) business relationships.